2003
DOI: 10.1023/b:neur.0000011331.58835.fd
|View full text |Cite
|
Sign up to set email alerts
|

5-ht2aReceptors in rat Sciatic Nerves and Schwann Cell Cultures

Abstract: Pharmacological approaches and optical recordings have shown that Schwann cells of a myelinating phenotype are activated by 5-HT upon its interaction with the 5-HT(2A) receptor (5-HT(2A)R). In order to further characterize the expression and distribution of this receptor in Schwann cells, we examined rat sciatic nerve and cultured rat Schwann cells using probes specific to 5-HT(2A)R protein mRNA. We also examined the endogenous sources of 5-HT in rat sciatic nerve by employing both histochemical stains and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Any of the >20 molecules released from mast-cell granules might be responsible for disruption of EGFR + nerves. Although NGF and serotonin are attractive candidates because Schwann cells express their receptors (Taniuchi et al, 1986;Gaietta et al, 2003), in preliminary experiments we found that blocking serotonin receptors did not affect EGFR + nerve pathology (not shown). The local environment can regulate the composition of mast-cell granules (Galli et al, 2005), and it is possible that the Schwann cell environment in EGFR + mice results in the de novo synthesis of mast-cell mediators that are responsible for the pathological progression in EGFR + nerves.…”
Section: Discussionmentioning
confidence: 86%
“…Any of the >20 molecules released from mast-cell granules might be responsible for disruption of EGFR + nerves. Although NGF and serotonin are attractive candidates because Schwann cells express their receptors (Taniuchi et al, 1986;Gaietta et al, 2003), in preliminary experiments we found that blocking serotonin receptors did not affect EGFR + nerve pathology (not shown). The local environment can regulate the composition of mast-cell granules (Galli et al, 2005), and it is possible that the Schwann cell environment in EGFR + mice results in the de novo synthesis of mast-cell mediators that are responsible for the pathological progression in EGFR + nerves.…”
Section: Discussionmentioning
confidence: 86%
“…Gaietta et al . () demonstrated that 5‐HT2A receptor mRNA and protein was expressed in rat sciatic nerves and cultured Schwann cells. The first evidence to suggest that 5‐HT receptors are expressed in OL lineage was from a study by Schaumburg et al .…”
Section: Discussionmentioning
confidence: 98%
“…Kahlil et al (41) report that cis-UCA does not directly cause degranulation of mast cells, but rather stimulates neuropeptide release from peripheral nerves, which in turn activates mast cells. It is interesting to note that peripheral nerves express 5-HT 2A receptors (42). Here again, it is not clear whether cis-UCA binding to 5-HT 2A receptors on nerve cells is causing the release of neuropeptides and subsequent mast cell activation.…”
Section: Discussionmentioning
confidence: 99%